Зміна форми леза ґрунтообробних знарядь при зношуванні - Козаченко, О. В.; Шкрегаль, О. М.; Каденко, В. С.; Kozachenko, Oleksiy; Shkrohal, Alexander; Kadenko, Volodimir (КНТУ, 2015)
В статті розглянуто напрямки підвищення технічного рівня робочих органів ґрунтообробних знарядь, зокрема культиваторів для міжрядного та суцільного обробітку ґрунту. Визначено напрямки удосконалення і підвищення довговічності культиваторних лап при застосуванні локального зміцнення твердосплавними матеріалами, встановлено можливість формоутворення зубчастого леза при експлуатації. The aim of this work is to study the dynamics of work wear tillage implements the example cultivators paws with curved shape and impact assessment geometrical parameters of local strengthening the interaction blade with an abrasive environment In the article the ways of raising the technical level of the working bodies of tillage implements, including cultivators for inter-row cultivation and continuous. Directions improved and durability cultivators paws when using local hardening carbide materials The possibility of forming toothed blades during operation Research deterioration of working with different types of cultivators strengthening indicates the feasibility of gear cutting surfaces can be formed during operation.
Changing the shape of the blade with wear tillage implements
Keywords: ґрунтообробні знаряддя; лапа культиватора; ґрунт; зношування; cultivating tools; paw cultivator; soil deterioration